KEMAMPUAN MEMBACA PEMAHAMAN BERDASARKAN TAKSONOMI BARRET PADA SISWA KELAS IV SD - Khotimah, Arif Widagdo, Sutaryono, Amalia Khusnul (Universitas Negeri Semarang, 2016)
The aimed of this study to identify the students’ ability in reading comprehension based on Barret Taxonomy at fourth grade students SD N Gugus Dwija Harapan Kecamatan Mijen. The writer conducted the research in beginning April until May 2016 and used descriptive research. Data of the research obtained the objective test and interview for the teachers and the students.The result of the study indicated that the average score obtained at literal comprehension level was 74%, the level of reorganized comprehension was 71%, the level of inferential comprehension was 68%, the level of evaluative comprehension was 56%, and the level of appreciation comprehension was 58%. According to interview for the students, in can be generalized that there were the difficulties in comprehending the text, such as 1) low vision condition; 2) disabilities to read fluently; 3) disabilities to paraphrase; 4) loss of words; 5) reduplicate words; 6) the difficulties to analyze the grammatical; 7) disabilities to identify the meaning word of sentences. According to the students problem, the writer suggest that 1) grouping the students spatially; 2) improving the students interest of reading; 3) using the strategy to identify the meaning; and 4) using the fun learning method.